The Clinical Characteristics of Other HLA-B Types in Chinese Ankylosing Spondylitis Patients - Wu, Xinyu; Wu, Jialing; Li, Xiaomin; Wei, Qiujing; Lv, Qing; Zhang, Pingping; Zheng, Xuqi; Chen, Zena; Cao, Shuangyan; Tu, Liudan; Gu, Jieruo (Frontiers in Medicine, 2021)
HLA-B27 has an established relationship with the development of Ankylosing spondylitis (AS). HLA-B*27:04 is the dominant subtype in Chinese AS patients. After HLA-B genotype from 307 subjects, we only found one HLA*27:04 homozygous AS person. After analyzing 206 HLA-B*27:04 samples (171 patients and 35 controls), we found 19.9% of patients were heterozygous with HLA-B*40:01 and HLA-B*27:04, which was statistically significant compared to the HLA-B*27:04 positive controls (P=0.002Fisher). In terms of clinical phenotype, patients both with HLA-B*46:01 and HLA-B*27:04 had more peripheral joint involvement (p=0.002, OR=3.961,95%CI 1.586-9.896) in HLA-B*27:04 AS. In HLA-B27(-) patients, HLA-B*15:02 was a significant risk element to peripheral joint involvement (OR=22,95%CI 1.924-251.539; p=0.01). So we think HLA-B*40:01, HLA-B*46:01, and HLA-B*15:02 can be the test indicators for AS diagnostic value.